PENINDAKAN CUKAI ILEGAL PADA KANTOR PENGAWASAN DAN PELAYANAN BEA CUKAI TIPE MADYA PABEAN C PAREPARE PERSPEKTIF HUKUM ISLAM - Rahmawati Rahmawati; Hardianto Hardianto; Adinda Cahya (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
The results of this study are that the Parepare Customs and Excise Enforcement conducts various strict and massive and continuous supervision including law enforcement efforts on various attempts to smuggle illegal, dangerous goods and captured goods will be destroyed and provide sanctions in the form of fines. The factors that hinder the directorate general of customs against the circulation of illegal excise, the factor of the lack of public awareness that still brings illegal excise goods into the Parepare area, the factor is still weak supervision and enforcement carried out by customs officials, there are several efforts made, namely preventive efforts, namely efforts made for prevention, repressive efforts, namely the form of activities carried out after the existence of preventive supervision, internal factors, namely the submission of additional personnel or employees, external factors, namely free and unclear area boundaries.